System justification: Experimental evidence, its contextual nature, and implications for social change. (19th September 2018) - Friesen, Justin P.; Laurin, Kristin; Shepherd, Steven; Gaucher, Danielle; Kay, Aaron C.
Abstract : We review conceptual and empirical contributions to system justification theory over the last fifteen years, emphasizing the importance of an experimental approach and consideration of context. First, we review the indirect evidence of the system justification motive via complimentary stereotyping. Second, we describe injunctification as direct evidence of a tendency to view the extant status quo (the way things are) as the way things should be. Third, we elaborate on system justification's contextual nature and the circumstances, such as threat, dependence, inescapability, and system confidence, which are likely to elicit defensive bolstering of the status quo and motivated ignorance of critical social issues. Fourth, we describe how system justification theory can increase our understanding of both resistance to and acceptance of social change, as a change moves from proposed, to imminent, to established. Finally, we discuss how threatened systems shore up their authority by co‐opting legitimacy from other sources, such as governments that draw on religious concepts, and the role of institutional‐level factors in perpetuating the status quo.